Kreatifitas Guru Menggunakan Media Pembelajaran Tematik Kelas V SDN 065854 Kecamatan Medan Helvetia Kota Medan - Harlen Simanjuntak; Eden A Sitompul (Fakultas Syariah IAIN Laa Roiba Bogor, 2021)
ABSTRACT The purpose of this study was to see the extent to which Teacher Creativity Using Thematic Learning Media Grade V SDN 065854 Medan Helvetia District Medan City. The subject of this research is the teacher and the method of this research is the analysis with the data collection techniques are observation, observation and documentation, Media in thematic learning is a means for teachers to deliver subject matter to students. Without the media of teaching and learning seem monotonous which causes students to feel bored so that the creativity of teachers is needed in the use of media. The purpose of this study is the author wants to explain about the creativity of teachers in the use of media in thematic learning in grade V SDN 065854 Medan Helvetia District, Medan City, data collection methods used are observation, interviews, and documentation. The results showed that the creativity of teachers in the use of instructional media in grade V SDN 065854 Medan Helvetia District, Medan City, included creativity in planning, developing, using, and evaluating learning media. Planning is an activity of the teacher choosing and studying the media. In the process of developing and using the media the teacher engages students in it. Media evaluation is done by evaluating the media itself, observing student behavior, and assigning or giving questions. Keywords: Teacher Creativity, Media, Thematic Learning, Elementary School.